2000
DOI: 10.1080/002072100132219
|View full text |Cite
|
Sign up to set email alerts
|

Electronically tunable current-mode active-only biquadratic filter

Abstract: This paper presents a realization of current-mode active-only ® lter. The proposed ® lter is constructed employing operational ampli® ers and operational transconductance ampli® ers (OTAs). The circuit can realize biquadratic transfer function, and the circuit characteristics can be electronically tuned through adjusting the transconductance gains of the OTAs. An example is given together with simulated result by PSPICE. The circuit con® guration is very suitable for implementation in both bipolar or CMOS tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 13 publications
(7 reference statements)
0
22
0
Order By: Relevance
“…where I A is the biasing current, B is the current multiplication factor and k 0 n W 1 L 1 is the process transconductance parameter of the input transistors (Tsukutani et al 2000). The inductance value is obtained as…”
Section: The Proposed Grounded Inductance Simulator Topologymentioning
confidence: 99%
See 2 more Smart Citations
“…where I A is the biasing current, B is the current multiplication factor and k 0 n W 1 L 1 is the process transconductance parameter of the input transistors (Tsukutani et al 2000). The inductance value is obtained as…”
Section: The Proposed Grounded Inductance Simulator Topologymentioning
confidence: 99%
“…In all reported papers on active-only filters and inductance simulators (Ishida et al 1986;Khan et al 1992;Higashimura 1993;Tsukutani et al 1996;Abuelma'atti and Alzaher 1997;Singh and Senani 1998;Ohtsuki et al 1999;Tsukutani et al 2000;Cicekoglu et al 2001;Ohtsuki et al 2001;Tsukutani et al 2001a,b;Tsukutani et al 2002;Minaei et al 2003a,b), a VOA is employed just for its integrator behaviour; they are operated in voltage or current mode regardless. These circuits have some disadvantages caused from using a VOA which operates in a limited frequency range determined by the integrator portion of its characteristic.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Analog filters are important building blocks and widely used for continuous-time signal processing [1]. In recent years, the current mode analogue signal processing circuit techniques have received wide attention due to the high accuracy, the wide signal bandwidth and the simplicity of implementing signal operations [2,3]. In filter circuit designs, current-mode filters are becoming popular since they have many advantages compared with their voltage-mode counter parts, the current-mode filters have large dynamic range, higher bandwidth, greater linearity, simple circuitry, and low power consumption etc.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that active filter designs utilizing the finite and complex gain nature of an internally compensated type operational amplifier are suitable for integrated circuit(IC) fabrication and high frequency operation. Several implementations in continuous-time filters using only active components are recently available in the literature [3][4][5][6] . They have been demonstrated that the realizations of the resistor-less and capacitor-less active-only circuit would be attractive for simplicity, integratability, programmability and wide frequency range of operation.…”
Section: Introductionmentioning
confidence: 99%